APD Analisis Faktor Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Petugas Laboratorium Di Kota Palopo Tahun 2024 - Tevri, Paula; Ilyas, Muh.; Saenuddin, Sudirman; Zamli, Zamli (An Idea Health Journal, 2025)
Laboratories are among the units most vulnerable to work-related accidents and occupational diseases. Despite this, adherence to the use of PPE (personal protective equipment ) in laboratories remains very low. This study aims to investigate the factors influencing PPE "Adherence to regulations among laboratory personnel" in Palopo City in 2024. “A quantitative research method with an observational approach was used, and chi-square statistical analysis was employed to assess the relationships”.The study population consisted of all laboratory personnel in Palopo City, including staff from two government hospitals and two private hospitals, totaling 50 respondents.Data were gathered via interviews and observations, and then analyzed with SPSS 26 for Windows.. The findings indicated no significant relationship between training and PPE compliance (p value = 0.729). “However, a significant relationship was found between PPE compliance and several factors: length of service (p~value = 0.025), facilities and infrastructure (p~value = 0.008), and institutional policies (p~value = 0.026)”. Based on these results, it is recommended to conduct training and workshops on PPE usage, increase socialization efforts regarding PPE, and provide recognition for those who adhere to PPE protocols.